Collaboration Between Actors In Disaster Mitigation In Manado City - Heydi Mayla Silvia Tumembow; Dian Ferriswara; Eny Haryati (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
Manado City is highly vulnerable to hydrometeorological disasters due to its geographical conditions, rapid and uncontrolled urbanization, and the intensifying impacts of climate change. These risks underline the importance of effective disaster mitigation strategies that go beyond government intervention and involve active participation from communities and non-governmental organizations. In this context, collaboration among various actors becomes a crucial foundation for developing an adaptive and participatory disaster governance system. This study aims to analyze the dynamics of actor collaboration in disaster mitigation efforts in Manado City, with particular emphasis on patterns of interaction, role distribution, and structural as well as cultural barriers that influence the effectiveness of multi-stakeholder synergy. Employing a qualitative case study approach, this research relies on secondary data gathered from official documents, government policy reports, and relevant academic publications. Data were analyzed using thematic analysis to identify key themes and relational dynamics among stakeholders. The findings reveal that although strong driving factors exist—such as a high level of disaster risk, increasing public awareness, and the availability of institutional frameworks—collaboration remains largely procedural and government-dominated, with limited engagement from non-government actors. Challenges such as weak trust among stakeholders, insufficient substantive dialogue, and the absence of an integrated disaster information system continue to hinder the realization of effective collaborative practices. The study concludes by highlighting the urgency of adopting a collaborative governance model that emphasizes equality, mutual trust, and meaningful participation. Theoretically, this research contributes to the discourse on disaster governance by providing insights into actor relations in a disaster-prone urban context. Practically, it proposes an adaptive collaboration framework that can be replicated in other cities facing similar disaster vulnerabilities, thereby strengthening resilience and community preparedness.